Análise computacional de sistema mecânico e fadiga de molas em suspensões de veículos off-road Baja SAE - Galvão, Lucas Thomé Brilhante (Universidade Federal de São Carlos, 2022)
Off-road vehicles are designed and built by teams of students in academic engineering extension projects to withstand various obstacles and adverse terrains, usually without pavement, which are difficult to navigate with regular passenger vehicles. The project and vehicle are presented and evaluated before judges at regional, national and international competitions, organized by SAE (Society of Automotive Engineers - Society of Autonomous Engineers). To guarantee the driver's safety, in addition to following the competition regulations, it is necessary to evaluate the components considering the loads that will be applied and the environment in which the vehicle will be inserted. In these assessments, a quantitative value is sought to allow setting goals, estimating limits and validating them. From this perspective, fatigue analysis is necessary to estimate the limits considering that the vehicle will be required repeatedly, as in the Enduro endurance test, a race lasting 4 consecutive hours. In this sense, simulations are carried out with representative models of the vehicle, usually built by a discrete dynamic system. Modal analysis provides model resonance frequencies, which can be used to evaluate critical points susceptible to loading. Performing a dynamic system analysis, considering as input the variations of an arbitrary terrain, the modal analysis was obtained, the tensions in the suspension springs were calculated and the fatigue damage caused by the loading on the springs was estimated. Therefore, the objective of this work is to present a way to estimate the vehicle's fatigue limit.
Computational analysis of mechanical system and spring fatigue in Baja SAE off-road vehicle suspensions
Keywords: Análise modal; Fadiga em molas; Baja SAE; ENGENHARIAS::ENGENHARIA MECANICA::MECANICA DOS SOLIDOS